2008
DOI: 10.1177/1352458508096877
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β bioactivity measurement in multiple sclerosis: feasibility for routine clinical practice

Abstract: Our data suggest that for IFN beta bioactivity screening a single post-injection measurement seems reasonable. However, MxA induction measurement based on both pre- and post-IFN beta injection samples at second measurement is somewhat more precise in determining ultimate IFN beta bioactivity status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In fact, MxA is a well defined ISG up-regulated by type I IFNs (IFNa and b) [30], but not by IFNc [31]. Along with several authors [1, 5-7, 14-16, 26], we have shown that MxA gene expression is significantly increased in treated compared to untreated patients [2,3,12,13,24], and that MxA gene expression is abolished by the presence of anti-IFNb BAbs or NAbs [2,4,[8][9][10][11][12][13][14][15][16] as well as by any other inhibiting factors [32]. Moreover, it was demonstrated that MxA gene expression correlates with altered expression of molecules involved in MS pathogenesis and/or IFNb clinical efficacy (e.g., matrix metalloproteinases, tumor necrosis factor-related apoptosis-inducing ligand [3,13,14]).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…In fact, MxA is a well defined ISG up-regulated by type I IFNs (IFNa and b) [30], but not by IFNc [31]. Along with several authors [1, 5-7, 14-16, 26], we have shown that MxA gene expression is significantly increased in treated compared to untreated patients [2,3,12,13,24], and that MxA gene expression is abolished by the presence of anti-IFNb BAbs or NAbs [2,4,[8][9][10][11][12][13][14][15][16] as well as by any other inhibiting factors [32]. Moreover, it was demonstrated that MxA gene expression correlates with altered expression of molecules involved in MS pathogenesis and/or IFNb clinical efficacy (e.g., matrix metalloproteinases, tumor necrosis factor-related apoptosis-inducing ligand [3,13,14]).…”
Section: Discussionmentioning
confidence: 80%
“…The problem of a false-negative result due to IFNb receptor saturation can be easily overcome by the following repetition of MxA mRNA quantification; particularly, reevaluating MxA gene expression after a 7-day withdrawal period and analyzing blood samples 12 h before and 12 h after IFNb injection [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since there are inter-individually different response curves of the MxA mRNA expression, a small proportion of patients may be classified false-positively [21][22][23]. To minimize this potential error it would be ideal to compare individual MxA mRNA responses on IFNb therapy with the respective responses at treatment initiation of the same individual [24]. In this issue of the Journal S. Malucchi et al have set out to evaluate BAbs and NAbs in 167 patients with MS after 1 year of treatment with IFNb.…”
mentioning
confidence: 99%